Molecular cloning and expression analysis of Aquaporin genes in pearl millet [Pennisetum glaucum (L) R. Br.] genotypes contrasting in their transpiration response to high vapour pressure deficits. (December 2017) - Reddy, Palakolanu Sudhakar; Tharanya, Murugesan; Sivasakthi, Kaliamoorthy; Srikanth, Mallayee; Hash, C. Tom; Kholova, Jana; Sharma, Kiran K.; Vadez, Vincent
Highlights: Identified pearl millet genotypes showing contrasting transpiration response to high vapor pressure deficit (VPD). Cloned seven PgAQP genes using homology based gene identification. PgAQP proteins were found to be evolutionarily closer to maize than rice. PgAQPs were induced in VPD-insensitive genotypes under low and high VPD conditions. PgPIP2;1, PgPIP1;2, PgTIP2;2 and PgPIP2;6 genes followed a diurnal rhythm of expression. Abstract: Pearl millet is a crop of the semi-arid tropics having high degree of genetic diversity and variable tolerance to drought stress. To investigate drought tolerance mechanism that possibly accounts for differences in drought tolerance, four recombinant inbred lines from a high resolution cross (HRC) were selected for variability in their transpiration rate (Tr) response to vapour pressure deficit (VPD) conditions. The differential Tr response of the genotypes to increased VPD conditions was used to classify the genotypes as sensitive or insensitive to high VPD. Aquaporin (AQP) genes PgPIP1;1, PgPIP1;2, PgPIP2;1, PgPIP2;3, PgPIP2;6, PgTIP1;1 and PgTIP2;2 were cloned. Phylogenetic analysis revealed that the cloned PgAQPs were evolutionarily closer to maize AQPs than to rice. PgAQP genes, including PgPIP1;1 and PgPIP2;6 in root tissue showed a significant expression pattern with higher expression in VPD-insensitive genotypes than VPD-sensitive genotypes under low VPD conditions (1.2 kPa) i.e when there is no high evaporative demand from the atmosphere. PgAQP genes (PgPIP2;1 in leaf and root tissues; PgPIP1;2 and PgTIP2;2 in leaf and PgPIP2;6 in root) followed a diurnal rhythm in leaves and roots that have either higher or lower expression levels at different time intervals. Under high VPD conditions (4.21 kPa), PgPIP2;3 showed higher transcript abundance in VPD-insensitive genotypes, and PgPIP2;1 in VPD-sensitive genotypes, while rest of the PgAQPs showed differential expression. Our current hypothesis is that these differences in the expression of AQP genes under different VPDs suggests a role of the AQPs in tuning the water transport pathways with variation between genotypes.